Knowledge of Radiation Exposure and it Risk among Radiographers and Radio Technologists - Sharma, B.R.; Singh, S.; Mandal, S.; Poudel, N. (Journal of Gandaki Medical College-Nepal, 2019)
Objective: The aim of this study was to assess the awareness, concern and practice on hazards of ionizing radiation and radiation protection among radiographers and technologists of Pokhara, Nepal and to evaluate the knowledge of radiation and its protection among them. Materials and Methods: A validated questionnaire was used to collect data from radiographers and Technologists. The survey included multiple choice questions (MCQs) related to demographic characteristics (age, gender), academic qualification, and knowledge of radiation and radiation protection. Obtained data were analyzed using Statistical Package for Social Science (SPSS) version 25 software and shown in frequency, percentages. Results: Among 103 participants, only 73.8% were NHPC registered and 46.7% had attended classes/seminar on the topic of radiation protection. Only 8.7% used dosimeters to measure the radiation dose. Among participants, 77.7% knew that annual whole-body dose for a radiation worker is 20 mSv and 87.4% knew that there should be distance of more than six feet from the X-ray tube while taking X-ray in the case of non-barrier protection. This study shows that the knowledge and the perceptions regarding radiation and its protection among the radiographers/technologist is just satisfactory and needs to be improved. Conclusion: Overall awareness and knowledge of radiation protection and radiological procedures of radiologic technologist were satisfactory. However, there were some question that they needed mandatory training and knowledge. Therefore, we recommend that further workshops, seminars, symposium, training courses and Continuing Medical Education (CME) programs are recommended on a regular basis in collaboration with ISSRT and other national and international organizations to raise the level of radiation awareness.